Assistive Technology: Sensor Bike Programmed (Propesor) as an Accommodative Aid for Children with Hearing Impairment - Njen, Usep; Hernawati, Tati (Angstrom Centre of Education, 2024)
This research discusses the design of assistive technology, especially the Sensor Bike Program (Propesor) as an accommodative aid for children with hearing impairments, this tool is a follow-up to the child's inability to listen to sounds or sounds around him. This puts them in a dangerous situation when driving, therefore an innovative tool is needed that can help them to recognise sounds or sounds around them. The research method used is descriptive qualitative with data collection techniques through observation, interviews, assessments, and documentation studies to collect comprehensive data as a basis for developing tools that suit the needs of children. The result of this research is a hypothetical design of the Sensor Bike Program (Propesor) and is ready to be realised into a valid tool.